Role of Wrist Arthroscopy in the Management of Established Scaphoid Nonunion - Karthik, Karuppaiah; Ali, Zaid; Colegate-Stone, Toby; Tavakkolizadeh, Adel; Compson, Jonathan (Journal of Hand and Microsurgery, 2019)
Introduction Patients with scaphoid nonunion and wrist pain may have a wide spectrum of potential concomitant pathologies that may be diagnosed and potentially managed arthroscopically. The aim of this study is to assess the usefulness of wrist arthroscopy in the assessment and treatment of scaphoid nonunion and any associated injuries.Materials and Methods We retrospectively reviewed 34 consecutive patients with established scaphoid nonunion between January 2006 and December 2012 who had undergone arthroscopic assessment. The average age of the patients was 40 years (range: 25–64), and all the patients had arthroscopic assessment of the wrist joint before definitive surgery. The patients with associated intra-articular problems, which could be addressed along with the scaphoid open reduction internal fixation (ORIF) and bone grafting (BG), had definite procedure in the same sitting. However, if the patients had major intra-articular pathology that needed change in the management plan, they had staged definitive treatment after discussing with them about the arthroscopic findings.Results Arthroscopic assessment of the 34 joints showed varying degrees of arthritis affecting radioscaphoid joint (41%) followed by injuries to the triangular fibrocartilage complex (TFCC) (35%), lunotriquetral ligament (LTL) tears (32%), and scapholunate ligament (SLL) injuries (26%). Concomitant procedures performed during the wrist arthroscopy included debridement of synovitis (62%), TFCC debridement (32%), loose body removal (17%), and DRUJ stabilization and TFCC repair (3%). Twenty-nine patients had arthroscopy and definitive procedure in the same sitting, and the remaining had staged or delayed definitive treatment.Conclusion Our study highlights the usefulness of wrist arthroscopy in assessment and management of the scaphoid nonunion and associated pathologies. Besides in 18% of our patients, the initial management plan changed after arthroscopy.Level of Evidence This is a Level IV study.
Keywords: scaphoid nonunion; carpal injuries; wrist arthroscopy; wrist injuries; carpal ligament injuries; arthritis